2011 International Electron Devices Meeting 2011
DOI: 10.1109/iedm.2011.6131650
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of high-density ReRAM ensuring 10-year retention at 85°C based on a newly developed reliability model

Abstract: A new oxygen diffusion reliability model for a high-density bipolar ReRAM is developed based on hopping conduction in filaments, which allows statistical predication of activation energy. The filament in the active cells is confirmed by EBAC and TEM directly for the first time. With optimized filament size, a 256-kbit ReRAM with long-term retention exceeding 10 years at 85˚C is successfully demonstrated. IntroductionResistance random access memory (ReRAM), which has the advantages of high speed and low power c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
105
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(110 citation statements)
references
References 5 publications
5
105
0
Order By: Relevance
“…The LRS conduction is believed to be governed by metallic conduction because of the Ohmic I-V characteristic and finite residual resistance at low temperature. In HRS, the I-V curve is well fitted to a straight line in ln(J) ∝ T Similar to [61], Zhang et al [64] also observed temperature dependency of the hopping conduction in TaOy/Ta2O5−x device. Two distinct slopes can be seen in the plot of ln(σ) against 1000/T.…”
Section: Hopping Conductionmentioning
confidence: 51%
See 1 more Smart Citation
“…The LRS conduction is believed to be governed by metallic conduction because of the Ohmic I-V characteristic and finite residual resistance at low temperature. In HRS, the I-V curve is well fitted to a straight line in ln(J) ∝ T Similar to [61], Zhang et al [64] also observed temperature dependency of the hopping conduction in TaOy/Ta2O5−x device. Two distinct slopes can be seen in the plot of ln(σ) against 1000/T.…”
Section: Hopping Conductionmentioning
confidence: 51%
“…While CF evolution is typically associated with thermal, electrical or ion migration [19,20], there is no consensus on the dominant conduction mechanism in resistive switching memory devices [21][22][23]. Among the commonly observed conduction mechanisms are: (i) Poole-Frenkel emission [24][25][26][27][28][29][30][31][32]; (ii) Schottky emission [33][34][35][36][37][38][39][40][41][42]; (iii) SCLC [43][44][45][46][47][48][49][50][51][52][53] (iv) trap-assisted tunneling [54][55][56][57][58][59]; and (v) hopping conduction [60][61][62][63][64][65]. To enhance the device performance and data retention property, it is crucial to identifying t...…”
Section: Introductionmentioning
confidence: 99%
“…[1,3] Various physical phenomena are known to lead to a non-volatile resistive switching effect which are related to different types of RRAM such as Thermo Chemical Memories (TCM) or Valency Change…”
Section: Introductionmentioning
confidence: 99%
“…In TaO Conversely, in bilayer memristors of TaO x and Ta, the lateral motion of oxygen vacancies or anions is thought to be key, with the oxygen concentration of a Ta rich conducting filament the purported state variable [83,86]. Quantitative models describing the physics of phenomena such as retention have been demonstrated [87], however, as summarized above, modeling of the physics of switching dynamics in TaOx memristors has been primarily qualitative. Here, we present a model based on microscopic ionic flux which quantitatively predicts the memristive operation of TaO x /Ta devices, providing close agreement with experimental resistive switching data.…”
Section: A Physical Model Of Switching Dynamics In Tantalum Oxide Memmentioning
confidence: 99%